2007
DOI: 10.1677/erc-07-0012
|View full text |Cite
|
Sign up to set email alerts
|

High tumoral levels of Kiss1 and G-protein-coupled receptor 54 expression are correlated with poor prognosis of estrogen receptor-positive breast tumors

Abstract: KiSS1 is a putative metastasis suppressor gene in melanoma and breast cancer-encoding kisspeptins, which are also described as neuroendocrine regulators of the gonadotropic axis. Negative as well as positive regulation of KiSS1 gene expression by estradiol (E 2 ) has been reported in the hypothalamus. Estrogen receptor a (ERa level is recognized as a marker of breast cancer, raising the question of whether expression of KiSS1 and its G-protein-coupled receptor (GPR54) is down-or upregulated by estrogens in bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
71
2
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(79 citation statements)
references
References 55 publications
0
71
2
6
Order By: Relevance
“…Moreover, the KiSS1 and GPR54 expression levels were higher in the ER-positive compared to in the ER-negative tumors. These data do not confirm the results of a study conducted by Marot et al, in which KiSS1 expression was negatively associated with ERα status (10). These authors also concluded that a high KiSS1 expression in ERα (+) breast tumors cells with poor prognosis may reflect hormonal resistance to E2.…”
Section: Gene Namecontrasting
confidence: 82%
See 1 more Smart Citation
“…Moreover, the KiSS1 and GPR54 expression levels were higher in the ER-positive compared to in the ER-negative tumors. These data do not confirm the results of a study conducted by Marot et al, in which KiSS1 expression was negatively associated with ERα status (10). These authors also concluded that a high KiSS1 expression in ERα (+) breast tumors cells with poor prognosis may reflect hormonal resistance to E2.…”
Section: Gene Namecontrasting
confidence: 82%
“…Moreover, the ERα level is a prognostic marker for breast tumors and a predictive factor of the response to endocrine therapy (9). Marot et al studied human breast cancer tumors and hypothesized that KiSS1 and GPR54 are estrogenregulated genes, and that their expression levels in these tumors should be analyzed, taking into account the expression profile and status of ERα (10). However, the precise mechanism, explaining the role of KiSS1/GPR54 in breast cancer cells and their loss or overexpression during metastasis, remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…It was then shown that this effect was not solely limited to this cancer type by detection in breast cancer (Lee and Welch, 1997b;Martin et al, 2005;Stark et al, 2005;Kostadima et al, 2007;Marot et al, 2007;Mitchell et al, 2007). Most reports associated loss of KISS1 with increasing cancer progression and metastases, although there are contradictions (Martin et al, 2005;Marot et al, 2007).…”
Section: A Metastasismentioning
confidence: 99%
“…It was then shown that this effect was not solely limited to this cancer type by detection in breast cancer (Lee and Welch, 1997b;Martin et al, 2005;Stark et al, 2005;Kostadima et al, 2007;Marot et al, 2007;Mitchell et al, 2007). Most reports associated loss of KISS1 with increasing cancer progression and metastases, although there are contradictions (Martin et al, 2005;Marot et al, 2007). To date, the metastasis suppressor activity of the kisspeptin system has been identified in thyroid (Ringel et al, 2002;Stathatos et al, 2005), ovarian Zhang et al, 2005;Gao et al, 2007;Hata et al, 2007), bladder (Sanchez-Carbayo et al, 2003), gastric (Dhar et al, 2004;Guan-Zhen et al, 2007;Yao et al, 2007), esophageal (Ikeguchi et al, 2004), hepatocellular (Ikeguchi et al, 2003;Hou et al, 2007;Schmid et al, 2007), pancreatic (Masui et al, 2004;Liang and Yang, 2007), and lung (Zohrabian et al, 2007) cancers.…”
Section: A Metastasismentioning
confidence: 99%
“…KiSS1 expression levels are increased in primary breast cancer lesions but reduced in metastatic lesions (22)(23)(24)(25), suggesting that KiSS1 may serve pleiotropic functions during breast cancer development and metastasis (20). While it was revealed that melatonin regulates KiSS1 expression in the hypothalamus in the brain (26,27), an association between melatonin and KiSS1 in cancer has not been identified.…”
Section: Introductionmentioning
confidence: 99%